The Effect Of Debt Policiy, Dividend Policy And Company Growth On Firm Value: Case Study of Manufacturing Companies Listed on the Jakarta Islamic Index for the Period 2018-2022 - Ramadanti, Anisya Lulu; Rusdi, Dedi (International Journal of Education, Information Technology, and Others, 2025)
This study aims to determine the effect of debt policy, dividend policy, and company growth on company value in manufacturing companies listed on the JII (Jakarta Islamic Index) for the 2018-2022 period. The period used in this study is 5 years, from 2018 to 2022. This study uses purposive sampling and hypothesis testing using multiple regression. Company value is investors' perception of the company's level of success, which is often associated with stock prices. High company value will increase market confidence in the company's performance and future prospects. Debt policy is measured using the debt-to-equity ratio (DER), dividend policy is measured using the dividend payout ratio (DPR), company growth is measured using total asset growth (TAG), and company value is measured using price book value (PBV). The results of this study indicate that debt policy has a positive and significant effect on company value, dividend policy has a negative but insignificant effect on company value, and company growth has a negative and significant effect on company value.